Meningkatkan Kemampuan Berhitung Anak Usia 5-6 Tahun melalui Penerapan Metode Penemuan Terbimbing Peserta Didik Kelompok B3 TK Negeri Pembina Mataram - Mukalipah, Tri Puspita (ARZUSIN, 2022)
The purpose of this study was to determine the increase in numeracy skills of children aged 5-6 years through the application of the guided discovery method for students in the B3 group of Mataram State Kindergarten for the 2021/2022 academic year. This research is a classroom action research. The subjects in this study were 15 students in the B3 TK Negeri Pembina Mataram group with 7 male students and 8 female students. Data collection techniques used are observation, documentation, and tests. Observation is used to collect data on interest in learning. The test is used to measure learning achievement in Mathematics. The data analysis used is descriptive qualitative and descriptive quantitative. The results showed that: The guided discovery method can improve the ability to learn to count in group B3 TK Negeri Pembina Mataram. Learning outcomes have increased with 60.00% learning mastery in the initial conditions to 80.00% in the first cycle to 100% in the second cycle classical student learning mastery has been achieved. From the student's activity has increased, student activity increased from the acquisition score of 79.17% in the first cycle, to 91.67% in the second cycle. Based on data analysis, it was found that the students' activities in the numeracy learning process using the guided discovery method were the most dominant working using tools/media, listening/paying attention to teacher explanations, and discussions between students/between students and teachers. So it can be said that student activities can be categorized as active. Meanwhile, teacher activity increased from the acquisition score of 77.78% in the first cycle to 95.83% in the second cycle. For teacher activities during learning, they have carried out the steps of the guided discovery method by optimizing the use of worksheets very well.